2014
DOI: 10.1002/anie.201310475
|View full text |Cite
|
Sign up to set email alerts
|

Dismutational and Global‐Minimum Isomers of Heavier 1,4‐Dimetallatetrasilabenzenes of Group 14

Abstract: Aromatic species with heavier Group 14 elements show remarkable differences in terms of stability, structure, and reactivity. Herein we report our experimental and theoretical investigations regarding isomers of germanium- and tin-containing benzene analogues E2Si4R6 (E=Ge, Sn). The germanium-substituted dismutational isomer with a tricyclic six-membered scaffold is isolable, but unlike the homonuclear Si6 analogue slowly rearranges even at room temperature to give the propellane-type global minimum isomer. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 56 publications
(37 reference statements)
3
43
0
2
Order By: Relevance
“…Computational studies clearly indicate however that with increasing number of heavy atoms the relative stability of nonplanar structures increases . Experimentally, this was demonstrated by the landmark investigations on Si 6 R 6 isomers by the groups of Sakurai and Scheschkewitz (Figure ) . These studies revealed the clear thermodynamic preference of non‐planar three‐dimensional arrangements such as 1 – 3 over planar, cyclic delocalized structures.…”
Section: Introductionmentioning
confidence: 62%
“…Computational studies clearly indicate however that with increasing number of heavy atoms the relative stability of nonplanar structures increases . Experimentally, this was demonstrated by the landmark investigations on Si 6 R 6 isomers by the groups of Sakurai and Scheschkewitz (Figure ) . These studies revealed the clear thermodynamic preference of non‐planar three‐dimensional arrangements such as 1 – 3 over planar, cyclic delocalized structures.…”
Section: Introductionmentioning
confidence: 62%
“…The surprisingly downeld shied signals (for tetracoordinate silicon atoms) had been rationalized by invoking magnetically induced cluster currents orin a complementary mannerby the strong LUMO contribution at this atom. 49,65,66 The 29 Si NMR chemical shis of the remaining cluster vertices are located in the typical range for saturated silicon atoms and vary only slightly with the introduced functionality. The longest wavelength absorption bands in the UV/Vis are observed at l max ¼ 459 nm (5a) and 477 nm (5b).…”
Section: Functionalization In Ligato Positionmentioning
confidence: 99%
“…Because of the brilliant development of synthetic chemistry in recent years, various 6π aromatic compounds containing heavier group 13-15 elements have been synthesized. [16][17][18][19] These developments have enabled opportunities to revisit the concept of aromaticity. Obviously, planarity is supposed to be one of the crucial requirements for aromaticity.…”
Section: Introductionmentioning
confidence: 99%